Transcription factor SS18L1 regulates the proliferation, migration and differentiation of Schwann cells in peripheral nerve injury - Qian, Tianmei; Qiao, Pingping; Lu, Yingnan; Wang, Hongkui (Frontiers in Veterinary Science, 2022)
Transcription factors bind to specific DNA sequences, modulate the transcription of target genes, and regulate various biological processes, including peripheral nerve regeneration. Our previous analysis showed that SS18L1, a gene encoding the transcription factor SS18-like protein 1, was differentially expressed in the distal sciatic nerve stumps after rat sciatic nerve transection injury, but its effect on peripheral nerve injury has not been reported. In the current study, we isolated and cultured primary Schwann cells, and examined the role of SS18L1 for the biological functions of the cells. Depletion of SS18L1 by siRNA in Schwann cells enhanced cell proliferation and inhibited cell migration, as determined by EdU assay and transwell migration assay, respectively. In addition, silencing of SS18L1 inhibited Schwann cell differentiation induced by HRG and cAMP. Bioinformatics analyses revealed an interaction network of SS18L1, including DF2, SMARCD1, SMARCA4 and SMARCE1, which may be implicated in the regulatory functions of SS18L1 on the proliferation, migration and differentiation of Schwann cells. In conclusion, our results revealed a temporal expression profile of SS18L1 in peripheral nerve injury and its potential roles during the process of nerve recovery.